The influence of knowledge management, knowledge workers and industrial revolution 4.0 towards competitiveness in Ivory Glove Sdn. Bhd. / Norzanah Mat Nor … [et al.] - Mat Nor, Norzanah; Abdul Wahab, Shazanah; Mohamad Rasidi, Nuur Mohamad Firdaus; Mohd Zaki, Nurnadhirah (Universiti Teknologi MARA, Perlis, 2023)
The aim of this study was to examine the influence of knowledge management, knowledge workers, and industrial revolution 4.0 (IR4.0) on the competitiveness of Ivory Glove Sdn Bhd. Two methods have been used in this study which were interviews and questionnaires. The interviews have been conducted with the Vice Chairman of Ivory Glove Sdn Bhd, and the management team. In addition, a total number of 106 employees in Ivory Glove Sdn Bhd have participated in this research study. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The research goals were met using reliability analysis, descriptive analysis, and correlation analysis. According to the findings, Ivory Glove Sdn Bhd's competitiveness is positively impacted by all the variables. However, this study also showed that Ivory Glove Sdn Bhd needs to put more emphasis on knowledge management for the business to be more competitive in the market and industry. The findings of this study have an important implication on how Ivory Glove Sdn Bhd's management could improve and focused on the competitiveness for its future growth. The results of this study provide information on how the company can achieve competitiveness by implementing change management related to knowledge management, upskilling the knowledge workers, and adapting industrial revolution 4.0 concepts in manufacturing operations. All the above are essential for an organization to remain competitive and relevant in the global market. Based on the findings, it can be concluded that there is a positive influence of knowledge management practice, knowledge workers’ contribution, and adaptation of industrial revolution 4.0 on innovation competitiveness in Ivory Glove Sdn Bhd. The adaptation of the fourth industrial revolution is critical in ensuring knowledge capture, knowledge creation, knowledge sharing, knowledge transfer, and knowledge application, particularly to assist management in exploring global networking and branding their product in Malaysia, as well as to improve knowledge workers' expertise and skills in becoming competitive in the digital era